2011
DOI: 10.1093/molbev/msr211
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial–Nuclear Interactions and Accelerated Compensatory Evolution: Evidence from the Primate Cytochrome c Oxidase Complex

Abstract: Accelerated rates of mitochondrial protein evolution have been proposed to reflect Darwinian coadaptation for efficient energy production for mammalian flight and brain activity. However, several features of mammalian mtDNA (absence of recombination, small effective population size, and high mutation rate) promote genome degradation through the accumulation of weakly deleterious mutations. Here, we present evidence for "compensatory" adaptive substitutions in nuclear DNA- (nDNA) encoded mitochondrial proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
200
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(208 citation statements)
references
References 57 publications
6
200
2
Order By: Relevance
“…Adaptive changes in one genome may alter fitness landscapes and facilitate subsequent adaptive changes in the other genome, though it is unclear what forces might trigger such runaway adaptive evolution in these systems. A more conventional model of compensatory change in the nucleus in response to accumulation of deleterious changes in asexual organelle genomes (Rand et al 2004;Osada and Akashi 2012) seems less likely, particularly for the CLP complex, given the evidence that accelerated rates of sequence evolution in the plastid-encoded clpP1 evolution are driven largely by positive selection (Erixon and Oxelman 2008;Sloan et al 2012a;Barnard-Kubow et al 2014).…”
Section: Antagonistic Coevolution and Plastid-nuclear Conflictmentioning
confidence: 99%
“…Adaptive changes in one genome may alter fitness landscapes and facilitate subsequent adaptive changes in the other genome, though it is unclear what forces might trigger such runaway adaptive evolution in these systems. A more conventional model of compensatory change in the nucleus in response to accumulation of deleterious changes in asexual organelle genomes (Rand et al 2004;Osada and Akashi 2012) seems less likely, particularly for the CLP complex, given the evidence that accelerated rates of sequence evolution in the plastid-encoded clpP1 evolution are driven largely by positive selection (Erixon and Oxelman 2008;Sloan et al 2012a;Barnard-Kubow et al 2014).…”
Section: Antagonistic Coevolution and Plastid-nuclear Conflictmentioning
confidence: 99%
“…Because fitness remains constant and genetic drift drives double-mutant substitution, we refer to such cases as "compensatory neutral" (CN). Weakly deleterious mutations can go to fixation at appreciable rates, and we refer to the restoration of fitness by subsequent, positively selected mutations as "compensatory weak selection" (CWS) (Osada and Akashi 2012). Note, however, that such mutations can confer large fitness benefits if they compensate for multiple deleterious fixations.…”
Section: Compensatory Protein Evolutionmentioning
confidence: 99%
“…The sample included female seniors majoring in philosophy, or those who recently earned a Bachelor's degree in it (N = 11, Age range: [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Participants were recruited via email by convenience sampling at colleges and universities in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…27 In 1923, the British government granted APOC control of an Iraqi railway line in Khanakin City, which gave APOC exclusivity for that particular line of 27½ miles in length. 28 According to Sluglett in Britain in Iraq, the Iraqi government concluded that more liberal control over the Iraqi railways may lead to a more amicable relationship with Britain. The Iraqi governments "only hope for amelioration lay in tinkering with the details of the Anglo-Iraqi relationship, and trusting that Britain might eventually be persuaded."…”
mentioning
confidence: 99%